Pelatihan Pemanfaatan Teknologi Digital Untuk Pencatatan dan Laporan Keuangan UMKM - Lindawati Lindawati; Wulandari Cahyani Putri; Gunung Subagyo Anom Haryoso (Jurnal Pengabdian Kepada Masyarakat Kalam, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in local economies, particularly in rural areas, where they are often the primary source of income and employment. Manual financial record-keeping methods often lead to errors in reporting and irregular bookkeeping. This results in the inability to monitor financial health in real time and make data-driven business decisions. Meanwhile, digital technology has advanced rapidly, with various applications and software specifically designed to assist with financial recording and reporting. This activity aims to increase knowledge by providing an understanding of the various types of digital technology that can be used for recording and reporting. This activity involved three lecturers from the Undergraduate Accounting Study Program, Faculty of Economics and Business, Pamulang University (UNPAM), who provided intensive training and mentoring to the management of MSMEs in Sukanegara Village.